The successful implementation of TPM in conjunction with EOM and 5S: a case presentation - Ahmed, Shamsuddin; Mohiuddin, A. K. M. (Asian Network for Scientific Information, 2005)
Certainly, manufacturing plants are encountering resource constraints. Limited equipment resources require close attention to make them useful every moment. This demands a total participatory equipment maintenance environment. Total Productive Maintenance (TPM) philosophy demonstrates that potential ability. In conjunction with Ecology Oriented Management (EOM)and Japaneses 5Ss housekeeping-norms, TPM can offer the successful achievement of total maintenance and pertinent productive goals. This study presents a case example on how a blend of these three concepts renders the highest effective potential in maintenance arena that can excel over maintenance goals. The methodology of this study is two fold: literature survey and case investigations in a large-scale company.